A review of classroom environment on student engagement in English as a foreign language learning - Ye, Xiaolan (Frontiers in Education, 2024)
The construct of learning engagement is receiving increasing attention since it has been proved by a majority of researches that higher learning engagement is linked to positive educational outcomes. While a list of learner-internal factors (e.g., academic emotions) and learner-external factors (e.g., teachers' working engagement) have been revealed as important antecedents of English as a foreign language (EFL) students' learning engagement, the role of classroom environment (CE) as a salient factor has received scant attention. Notably, to the best of the author's knowledge, no review study has been conducted on this issue. Thus, inspired by this gap, the purpose of the present review article is to evaluate the existing literature on the influence of CE on EFL students' learning engagement, which is a relatively less charted territory but with great significance, to illuminate the ways of securing, maintaining and enhancing students' engagement in foreign language classrooms by means of creating a positive CE. The central information of the article is organized into three parts. First, based on educational research, an overview of the constructs of learning engagement and CE is explicated. Second, the influence of CE on EFL learners' engagement is highlighted.At last, implications of the existing studies are summarized and suggestions for further studies are provided.